On the malleability of gender attitudes: Evidence from implicit and explicit measures in Tunisia - Eleonora Nillesen; Michael Grimm; Micheline Goedhuys; Ann-Kristin Reitmann; Aline Meysonnat (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
We use an implicit association test (IAT) next to a set of direct survey questions to measure implicit and explicit gender attitudes in Tunisia. Tunisia is among the most advanced countries in the Arab region in terms of women rights and legal reforms that shall strengthen the position of women. Yet, there still exists a tension between the law and what is practiced. We examine the malleability of these attitudes using (i) a randomized video intervention and (ii) natural variation in interviewer characteristics with respect to gender and perceived religiosity. The video has no average impact, which is consistent with the idea that in a highly polarized society like Tunisia such an intervention only affects attitudes of specific groups in a society. We indeed find that the video mitigates the implicit gender bias only among a specific subpopulation: conservative women. We also confirm the presence of interviewer effects, both for implicit and explicit attitudes. These effects are more pronounced for explicit attitudes, which may suggest social desirability at work. We discuss the implications of our findings for further research and policies targeted at gender attitudes.
Keywords: C83; D91; O12; 330; women's empowerment; implicit association test; interviewer effects; Middle East and North Africa region